BIOCHEMICAL AND IN SILICO CLOTTING ACTIVITY OF LATEX FROM ASCLEPIAS CURASSAVICA.L - KARPAGAM .N; VISWANATHAN.S; PRABHU.S; SULOCHANA SOMASUNDARAM; SIVANANDHAM.M (International Journal of Pharma and Bio Sciences, 2013)
The crude latex extract of Asclepias curassavica contains many proteins and exhibits strong proteolytic activity. The study was done to identify the clotting factor present in the latex of Asclepias curassavica and to analyze the thrombin like activity of the clotting factor. In this study the plant latex from Asclepias curassavica was collected and extracted the proteins. Proteolytic assays and inhibitor assays were carried out in the crude sample extract. The docking studies were carried out using Bioinformatics tools. The plasma clotting time was reduced from 143 seconds to 56 seconds in the presence of the crude latex extract. Reduction in coagulation time was observed with increase in the concentration of crude extract. In-silico studies showed that the cysteine protease of Asclepias curassavica interacts with the coagulation factors. The Factors VIII and XI there by leading to clot formation. Hence, from this research, it was proved that the compounds, Asclepain cI and cII, were readily involved in the clotting activity and were also found to reduce the time of coagulation.